Rivaroxaban or vitamin-K antagonists following early endovascular thrombus removal and stent placement for acute iliofemoral deep vein thrombosis. Issue 172 (December 2018) - Sebastian, Tim; Hakki, Lawrence O.; Spirk, David; Baumann, Frederic A.; Périard, Daniel; Banyai, Martin; Spescha, Rebecca S.; Kucher, Nils; Engelberger, Rolf P.
Abstract: Background: The optimal anticoagulant following catheter-based therapy of acute iliofemoral deep vein thrombosis (IFDVT) is unknown. Methods: From the Swiss Venous Stent registry, an ongoing prospective cohort study, we performed a subgroup analysis of patients with acute IFDVT who underwent catheter-based early thrombus removal followed by nitinol stent placement. Duplex ultrasound and Villalta scores were used to determine patency rates and incidence of the post-thrombotic syndrome (PTS) in patients treated with either rivaroxaban (n = 73) or a vitamin K-antagonist (VKA; n = 38) for a minimum duration of 3 months. Results: Mean follow-up duration was 24 ± 19 months (range 3 to 77 months). Anticoagulation therapy was time-limited (3 to 12 months) in 56% of patients (47% in the rivaroxaban group and 58% in the VKA group, p = 0.26), with shorter mean duration of anticoagulation in the rivaroxaban group (180 ± 98 days versus 284 ± 199 days, p = 0.01). Overall, primary and secondary patency rates at 24 months were 82% (95%CI, 71–89%) and 95% (95%CI, 87–98%), respectively, with no difference between the rivaroxaban (87% [95%CI, 76–94%] and 95% [95%CI, 85–98%]) and the VKA group (72% [95%CI, 52–86%] and 94% [95%CI, 78–99%]; p > 0.10 for both). Overall, 86 (86%) patients were free from PTS at latest follow-up, with no difference between the rivaroxaban and the VKA groups (57 [85%] versus 29 [88%]; p = 0.76). Two major bleeding complications (1 in each group) occurred in the peri-interventional period, without any major bleeding thereafter. Conclusions: In patients with acute IFDVT treated with catheter-based early thrombus removal and venous stent placement, the effectiveness and safety of rivaroxaban and VKA appear to be similar. Clinical trial registration: The study is registered on the National Institutes of Health website (ClinicalTrials.gov ; identifierNCT02433054 ). Highlights: Endovascular therapy for acute iliofemoral deep vein thrombosis reduces the risk of the postthrombotic syndrome. There is great inconsistency in the use of antithrombotic agents after placement of venous stents. Rivaroxaban appears to be as effective as vitamin K antagonists for preserving patency of the treated vein.